Portable ECMO and transport - Pranay Oza; Venkat Goyal (Wolters Kluwer Medknow Publications, 2017)
Patient transport is an integral part of the management of critically ill patients & even with patient on ECMO (Extracorporeal membrane oxygenation). Inter and Intra hospital transfer of patients is often needed for diagnostic or therapeutic interventions. Even critically illpatients can be transported safely by experienced and trained personnel using appropriate equipment. However, the transfer process carries its own risk and a poorly and hastily conducted transfer could lead to adverse events. This article describes the Indian scenario regarding portable ECMO and transports carried out by team at Riddhivinayak critical care and cardiac centre (RVCC), Mumbai since 2010 at centres nationwide and all the technical and logistic issues are detailed.